High ambient levels of grass, weed and other pollen are associated with asthma admissions in children and adolescents: A large 5‐year case‐crossover study. Issue 11 (10th August 2018) - Shrestha, Som K.; Katelaris, Constance; Dharmage, Shyamali C.; Burton, Pamela; Vicendese, Don; Tham, Rachel; Abramson, Michael J.; Erbas, Bircan
Summary: Background: Pollen is an important aeroallergen that triggers asthma exacerbations in children, but we know little about the impact of different pollen types in cities with varying climatic conditions and pollen seasons. Objectives: We aimed to assess the role of ambient level of different types of pollen on a large time series of child and adolescent asthma hospitalizations in Sydney, Australia. Methods: Childhood asthma hospitalization and the daily ambient pollen concentrations of different species were collected in South‐West Sydney. With a bidirectional case‐crossover design, we fitted conditional logistic regression models to measure the associations between instantaneous and up to 3 days lagged effects of pollen concentrations on asthma hospitalizations after controlling for potential confounders and testing for interactions. Results: A total of 2098 children, more boys (59.7%) and 2‐5 years old (62.6%), were hospitalized due to asthma. The geometric mean concentration of Cupressus, 7.88 [5.02] grains/m 3, was the highest during the study period. The increase from 75th to 90th percentile of grass (OR = 1.037, 95% CI 1.005‐1.070), weed other than Plantago species (OR = 1.053, 95% CI 1.009‐1.098) and unclassified pollen (OR = 1.034, 95% CI 1.010‐1.058) were significantly associated with the odds of asthma hospitalizations. Boys were at greater risk of asthma exacerbations associated with grass (OR = 1.046, 95% CI 1.003‐1.090) and unclassified pollen (OR = 1.041, 95% CI 1.010‐1.073). There was evidence of effect modification by age groups for Cupressus, conifer, total tree and total pollen. Conclusions: Although boys are more vulnerable to grass pollen, weed, and other pollen are also important triggers of asthma exacerbations in all children and adolescents. These findings are important for urban green space planning and the development of pollen monitoring systems for families with children at risk of asthma exacerbations during peak pollen seasons.